Dark blue solid-state fluorescent carbon quantum dot as well as preparation method and application thereof

Through the dark blue solid fluorescent carbon quantum dots composed of carbon, hydrogen, and oxygen composed of solvent thermal reactions, the problem of the lack of dark blue solid fluorescence in the existing technology has been solved, the high -effective dark blue fluorescent launch is achieved, and production costs are reduced.

CN119349554APending Publication Date: 2025-01-24SOUTHERN UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411309480.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The prior art lacks dark blue solid fluorescent carbon quantum dots with emission wavelengths less than 450nm, and commonly used solutions will introduce heavy elements, destroy the biosafety of carbon quantum dots and increase production costs.

Method used

Deep blue solid-state fluorescent carbon quantum dots composed of three elements: carbon, hydrogen and oxygen are prepared through solvothermal reaction. The maximum emission wavelength is 420nm~450nm, the particle size is 3nm~7nm, and it does not contain heavy elements.

Benefits of technology

A deep blue fluorescent launch with high efficiency in solid state has been realized, especially the quantum efficiency at 425nm at 425nm reaches 28 %, and reduces production costs, suitable for industrialized production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119349554A_ABST
    Figure CN119349554A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of carbon quantum dot materials, in particular to a dark blue solid-state fluorescent carbon quantum dot as well as a preparation method and application thereof. The dark blue solid-state fluorescent carbon quantum dot is composed of three elements of carbon, hydrogen and oxygen, and can be excited by light of 300 nm to 400 nm, and the maximum emission wavelength is 420 nm to 450 nm. The dark blue solid-state fluorescent carbon quantum dot is composed of three elements of carbon, hydrogen and oxygen, has the advantages of being environmentally friendly, free of pollution, free of biological toxicity and the like, can be excited by ultraviolet-near ultraviolet light in a solid state and emit dark blue fluorescence within 450 nm, has high solid-state fluorescence quantum efficiency, especially can have 28% quantum efficiency at 425 nm, and can be used for preparing the dark blue solid-state fluorescent carbon quantum dot. The application of the carbon quantum dots in the aspect of fluorescence color development is facilitated. Moreover, the preparation method disclosed by the invention is simple and easy to implement, convenient and rapid, low in production cost, low in requirements on equipment and easy for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of carbon quantum dot materials, and in particular to a deep blue solid fluorescent carbon quantum dot and a preparation method and application thereof. Background Art

[0002] Quantum dot materials have properties different from macroscopic materials due to the quantum confinement effect, and have had a huge impact in the fields of life sciences and information technology. As a new member of the quantum dot family, carbon quantum dots are non-toxic and pollution-free, have adjustable emission, and upconversion luminescence compared to semiconductor quantum dots. They are a new generation of display and anti-counterfeiting materials with great potential and have strong development potential. However, so far, carbon quantum dots prepared by conventional means have a distance between adjacent carbon quantum dots less than the Forster distance in the solid state due to the intermolecular attraction factor, resulting in resonant energy transfer and solid-state fluorescence quenching. For this reason, carbon quantum dots have low quantum efficiency or no fluorescence in the solid powder state, which greatly hinders their long-term development in the field of solid luminescence.

[0003] At present, in order to solve this problem, researchers usually use the method of adding large particle molecules as cross-linking agents to distribute carbon quantum dots around the cross-linked network composed of large particles (usually heavy elements), increase the distance between molecules, and improve their quantum efficiency in the solid state. For example, Wei et al. (Scalable Synthesis of Green Fluorescent Carbon Dot Powders with Unprecedented Efficiency, Advanced Optical Materials, 2020, 8, 1901938, DOI: 10.1002 / adom.201901938) added additional sodium hydroxide during the synthesis of carbon quantum dots, and embedded the carbon quantum dots in situ in the sodium hydroxide crystal matrix, so that the carbon quantum dots have the ability to resist self-quenching, and achieved a green solid-state fluorescence with a quantum efficiency of 75.9%. Similarly, Li et al. (High-Efficiency Luminescent Solar Concentrators Based on Carbon Dots with Simultaneously Ultrabright Solid-State and Liquid-State Luminescence, Advanced Functional Materials, 2024, 2404473, DOI: 10.1002 / adfm.202404473) added barium chloride during the preparation of carbon quantum dots to synthesize barium-doped carbon quantum dots, and achieved 88% solid-state fluorescence quantum efficiency through the cross-linking enhancement effect with polyvinylpyrrolidone (PVP). Although excellent optical properties can be achieved by introducing an external cross-linked network to resist self-quenching, this method will increase the cost to a certain extent, and the synthesis process is more cumbersome. In addition, due to the introduction of heavy elements such as barium, silicon, and sodium, the unique biosafety of carbon quantum dots is destroyed, which limits its application in some aspects.

[0004] In addition, the emission range of the current mainstream solid-state fluorescent carbon quantum dots is mainly concentrated in blue-green light, and the emission wavelength is generally 450nm-550nm. There is a lack of deep blue solid-state fluorescent carbon quantum dots with an emission wavelength less than 450nm, which imposes great restrictions on the application of carbon quantum dots.

[0005] Therefore, the prior art still needs to be improved and developed. Summary of the invention

[0006] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide a deep blue solid-state fluorescent carbon quantum dot that does not contain heavy elements such as barium, silicon, and sodium, and a preparation method and application thereof, aiming to solve the problem of the existing lack of deep blue solid-state fluorescent carbon quantum dots with an emission wavelength less than 450nm and the safety of solid-state fluorescent carbon quantum dots.

[0007] The technical solution of the present invention is as follows:

[0008] The first aspect of the present invention provides a deep blue solid fluorescent carbon quantum dot, wherein the deep blue solid fluorescent carbon quantum dot is composed of three elements: carbon, hydrogen and oxygen, and can be excited by light of 300nm to 400nm, and the maximum emission wavelength is 420nm to 450nm.

[0009] Optionally, the maximum emission wavelength is 420nm-435nm.

[0010] Optionally, in the deep blue solid fluorescent carbon quantum dots, the molar ratio of carbon element is 55%-70%, and the molar ratio of oxygen element is 30%-45%.

[0011] Optionally, the particle size of the deep blue solid fluorescent carbon quantum dots is 3 nm to 7 nm.

[0012] The second aspect of the present invention provides a method for preparing the deep blue solid fluorescent carbon quantum dots of the present invention, which comprises the steps of:

[0013] A precursor containing only three elements, carbon, hydrogen and oxygen, is mixed with a solvent to carry out a solvothermal reaction to obtain a crude product;

[0014] The crude product is subjected to freezing and drying treatment to obtain the dark blue solid fluorescent carbon quantum dots.

[0015] Optionally, the ratio of the mass of the precursor to the volume of the solvent is 0.1 g to 1 g: 10 mL to 30 mL.

[0016] Optionally, the precursor is citric acid, and the solvent is an alcohol solvent or deionized water.

[0017] Optionally, the alcohol solvent is methanol.

[0018] Optionally, the reaction temperature of the solvent thermal reaction is 140° C. to 200° C., and the reaction time is 2 h to 12 h.

[0019] The third aspect of the present invention provides an application of the deep blue solid fluorescent carbon quantum dots described in the present invention in fluorescent color development.

[0020] Beneficial effects: The deep blue solid fluorescent carbon quantum dots of the present invention are composed of three elements: carbon, hydrogen and oxygen, and have the advantages of being environmentally friendly, pollution-free and biologically non-toxic. In a solid state, they can be excited by ultraviolet-near ultraviolet light and emit deep blue fluorescence within 450nm, and have a high solid-state fluorescence quantum efficiency, especially a quantum efficiency of 28% at 425nm, which helps promote the application of carbon quantum dots in fluorescent color development. In addition, the preparation method of the present invention is simple and easy, convenient and fast, with low production cost, low requirements for equipment, and easy industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is the TEM image of the dark blue solid-state fluorescent carbon quantum dots prepared in Example 1.

[0022] Figure 2 This is the XPS graph of the dark blue solid-state fluorescent carbon quantum dots prepared in Example 1.

[0023] Figure 3 This is the XPS graph of the carbon quantum dots prepared in Comparative Example 1.

[0024] Figure 4 This is the fluorescence spectrum of the dark blue solid-state fluorescent carbon quantum dots prepared in Example 1 under excitation at a wavelength of 340 nm.

[0025] Figure 5 These are photos of deep blue solid-state fluorescent carbon quantum dots under sunlight and ultraviolet light. DETAILED DESCRIPTION

[0026] The present invention provides a deep blue solid fluorescent carbon quantum dot and a preparation method and application thereof. In order to make the purpose, technical scheme and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0027] Solid-state fluorescent carbon quantum dots have unique importance and potential application advantages: 1. Practical application requirements: In practical applications, many scenarios require materials to exist in solid form. For example, devices such as light-emitting diodes (LEDs), displays, sensors, and lasers often rely on solid-state luminescent materials. Therefore, studying the solid-state fluorescence of carbon quantum dots will help expand their applications to these areas. 2. Improved stability: Solid-state materials are generally more stable than liquid materials, especially during long-term storage, transportation, and use. And solid-state carbon quantum dots may perform better in optical stability, chemical stability, and thermal stability, which is very important for practical applications. 3. Environmentally friendly materials: Carbon quantum dots themselves are environmentally friendly materials. Developing them into solid-state fluorescent materials can replace traditional rare earth elements or heavy metal-based luminescent materials, thereby reducing the impact on the environment. 4. Versatility: Solid-state fluorescent carbon quantum dots can be compounded with other materials to form new functional materials, such as for bioimaging, sensing, catalysis, and other applications. These composite materials may have unique properties different from those in the liquid state, expanding the application prospects of carbon quantum dots. 5. Convenience and controllability: Solid-state materials are easier to operate and control during preparation and use, and can be easily prepared into light-emitting devices or coatings of different shapes, sizes and structures, which is particularly important in the manufacture of electronic and optoelectronic devices.

[0028] Therefore, by studying the solid-state fluorescence properties of carbon quantum dots, we can better understand and optimize their performance in different applications, thereby promoting the application of such materials in a wider range of fields. However, the prior art lacks research on dark blue solid-state fluorescent carbon quantum dots with an emission wavelength of less than 450nm. Based on this, an embodiment of the present invention provides a dark blue solid-state fluorescent carbon quantum dot, wherein the dark blue solid-state fluorescent carbon quantum dot is composed of three elements of carbon, hydrogen, and oxygen, and can be excited by light of 300nm to 400nm (for example, 300nm, 310nm, 320nm, 330nm, 340nm, 350nm, 360nm, 370nm, 380nm, 390nm, 400nm, etc.), and the maximum emission wavelength is 420nm to 450nm (for example, 420nm, 425nm, 430nm, 435nm, 440nm, 445nm, 450nm, etc.).

[0029] The deep blue solid-state fluorescent carbon quantum dots in the embodiment of the present invention are composed of three elements: carbon, hydrogen, and oxygen, and do not contain heavy elements (barium, silicon, sodium, etc.). They have the advantages of being environmentally friendly, pollution-free, and biologically non-toxic. In a solid state, they can be excited by 300nm to 400nm light (ultraviolet-near ultraviolet light), emitting deep blue fluorescence with a maximum emission wavelength of 420nm to 450nm, and have a high solid-state fluorescence quantum efficiency, which helps to promote the application of carbon quantum dots in fluorescent color development.

[0030] Solid-state fluorescent carbon quantum dots in the prior art generally add some macromolecules or polymers as a matrix to eliminate aggregation quenching. When the concentration is too high, the load of the medium or network is greatly increased, which will also lead to aggregation quenching, which limits the quantum yield (QY) and emission regulation range of carbon quantum dots in solid-state fluorescence. In addition, the prior art increases the particle spacing of carbon quantum dots by adding external media, and does not achieve the intrinsic solid-state fluorescence of carbon quantum dots. The dark blue solid-state fluorescent carbon quantum dots in the embodiment of the present invention only contain three elements of carbon, hydrogen and oxygen, and do not introduce external network structures and polymer surfaces. The focus is on regulating the distribution of elements in carbon quantum dots, fundamentally solving the aggregation quenching problem of carbon quantum dots, and achieving the intrinsic solid-state fluorescence of carbon quantum dots.

[0031] The dark blue solid-state fluorescent carbon quantum dots in the embodiment of the present invention have abundant oxygen groups (such as R-OH) on their surface, which can significantly increase the distance between the particles, weaken the aggregation quenching (ACQ) phenomenon, and enhance their solid-state fluorescence performance.

[0032] In one embodiment, the maximum emission wavelength is 420 nm to 435 nm.

[0033] In one embodiment, in the deep blue solid fluorescent carbon quantum dots, the molar ratio of carbon element is 55%-70%, and the molar ratio of oxygen element is 30%-45%.

[0034] In one embodiment, the quantum efficiency of the deep blue solid fluorescent carbon quantum dots is 2% to 30%.

[0035] In one embodiment, the quantum efficiency of the deep blue solid fluorescent carbon quantum dots is 15% to 30%.

[0036] In one embodiment, the deep blue solid fluorescent carbon quantum dots are composed of three elements: carbon, hydrogen, and oxygen, and can be excited by 340 nm light, with a maximum emission wavelength of 425 nm and a quantum efficiency of 28.81%.

[0037] In one embodiment, the particle size of the deep blue solid fluorescent carbon quantum dots is 3 nm to 7 nm.

[0038] The embodiment of the present invention further provides a method for preparing the deep blue solid fluorescent carbon quantum dots of the present invention, which comprises the steps of:

[0039] A precursor containing only three elements, carbon, hydrogen and oxygen, is mixed with a solvent to perform a solvothermal reaction to obtain a crude product;

[0040] The crude product is subjected to freezing and drying treatment to obtain the dark blue solid fluorescent carbon quantum dots.

[0041] The preparation method of the embodiment of the present invention is simple, convenient, fast, low in production cost, low in equipment requirements, and easy to industrialize. No special protection is required during the preparation process, and it is environmentally friendly, pollution-free, and non-toxic to organisms.

[0042] In one embodiment, the ratio of the mass of the precursor to the volume of the solvent is 0.1 g to 1 g: 10 mL to 30 mL. Within this mass-to-volume ratio range, oxygen elements can fully form R-OH groups in the reaction and distribute them on the surface of carbon quantum dots, thereby enhancing their solid-state fluorescence properties. In addition, the amount of precursor should not be too much. The more precursors there are, the lower the quantum efficiency.

[0043] In one embodiment, the precursor is citric acid.

[0044] In one embodiment, the solvent is an alcohol solvent or deionized water, preferably an alcohol solvent, and more preferably methanol. Alcohol solvents are rich in oxygen elements, which can oxidize carbon quantum dots during the reaction. After the reaction, the surface of the carbon quantum dots contains abundant R-OH groups, which can significantly increase the distance between the particles, weaken the aggregation quenching phenomenon, and enhance the solid-state fluorescence performance.

[0045] In one embodiment, when the solvent is methanol, the quantum efficiency of the prepared deep blue solid fluorescent carbon quantum dots is 15% to 30%.

[0046] In one embodiment, the reaction temperature of the solvothermal reaction is 140°C to 200°C (e.g., 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, etc.), and the reaction time is 2h to 12h (e.g., 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, etc.). Within the reaction temperature and reaction time range, the reaction can be fully carried out without causing damage to the precursor or product.

[0047] In one embodiment, the steps of mixing a precursor containing only three elements of carbon, hydrogen and oxygen with a solvent and performing a solvothermal reaction to obtain a crude product specifically include:

[0048] S1, mixing a precursor containing only three elements of carbon, hydrogen and oxygen with a solvent, and dissolving them by ultrasonication to obtain a mixed solution;

[0049] S2, stirring the mixed solution at a first temperature for a first time, heating it to a second temperature for a second time to perform a solvent thermal reaction, and then cooling it to room temperature within a third time to obtain a crude product.

[0050] In one embodiment, the first temperature is 25° C. to 30° C., and the first time is 1 h to 3 h.

[0051] In one embodiment, the heating rate of the heating is 1°C / min to 3°C / min, the second temperature is 140°C to 200°C, and the second time is 2h to 12h.

[0052] In one embodiment, the cooling rate is 1°C / min to 3°C / min, and the third time is 1h to 3h.

[0053] In one embodiment, the steps of freezing and drying the crude product specifically include:

[0054] The crude product is frozen at -40°C to -90°C (for example, -40°C, -50°C, -60°C, -70°C, -80°C, -90°C, etc.) for 12h to 36h (for example, 12h, 20h, 24h, 30h, 36h, etc.), and then dried at a pressure of 1Pa to 30Pa (for example, 1Pa, 3Pa, 5Pa, 8Pa, 10Pa, 15Pa, 20Pa, 25Pa, 30Pa, etc.) for 72h to 168h (for example, 72h, 96h, 120h, 144h, 168h, etc.).

[0055] The freezing and drying process in the embodiment of the present invention is to extract the carbon quantum dots from the solution, prepare them into fluffy powder, and test the solid-state fluorescence of the carbon quantum dots in the powder state.

[0056] The embodiment of the present invention further provides an application of the deep blue solid fluorescent carbon quantum dots described in the present invention in fluorescent color development.

[0057] The present invention will be further described below by means of specific examples.

[0058] Example 1

[0059] This embodiment provides a deep blue solid fluorescent carbon quantum dot and a preparation method thereof, which is as follows:

[0060] The raw material 0.25g citric acid and 20mL methanol are placed in a polytetrafluoroethylene (PTFE) reactor liner with a capacity of 50mL, and placed in an ultrasonic machine for 60min to fully mix the raw materials and dissolve them to obtain a mixed solution. The mixed solution is then loaded into a stainless steel reactor shell, and a solvent thermal reaction is carried out in a homogeneous reactor. First, it is rotated and stirred for 2h at 30°C, then heated to 180°C for 2h at a heating rate of 1.5°C / min, kept at 180°C for 4h, and then cooled to room temperature for 2h at a cooling rate of 1.5°C / min to obtain a crude product. Finally, the crude product is poured into a plastic bottle, 80mL of deionized water is added and stirred to obtain a sample solution, and then the sample solution is placed in a freeze dryer, frozen at -50°C for 24h, then dried at a pressure of 8Pa for 168h, and the sample is collected and fully ground to obtain a pure white powder, which is the dark blue solid fluorescent carbon quantum dots.

[0061] Example 2

[0062] The preparation method of Example 2 is basically the same as that of Example 1, except that in the solvothermal reaction, the mixture is first stirred at 30°C for 2h, then heated to 200°C at a heating rate of 1.5°C / min for 2h, kept at 200°C for 4h, and then cooled to room temperature at a cooling rate of 1.5°C / min for 2h to obtain a crude product. Finally, dark blue solid fluorescent carbon quantum dots are prepared.

[0063] Example 3

[0064] The preparation method of Example 3 is basically the same as that of Example 1, except that 20 mL of methanol is replaced by 20 mL of deionized water. Finally, dark blue solid fluorescent carbon quantum dots are prepared.

[0065] Comparative Example 1

[0066] The preparation methods of Comparative Example 1 and Example 3 are basically the same, except that 130 μL of ethylenediamine is additionally added as a raw material. Finally, carbon quantum dots are prepared in the form of brown-red powder.

[0067] The carbon quantum dot samples prepared in Examples 1-3 were characterized in terms of morphology. Figure 1 This is a TEM (transmission electron microscope) image of the dark blue solid fluorescent carbon quantum dots prepared in Example 1. It can be seen that the particle size of the dark blue solid fluorescent carbon quantum dots is about 5 nm, and has a clear lattice and uniform particles. The TEM images of Examples 2-3 are similar to those of Example 1.

[0068] The carbon quantum dot samples prepared in Examples 1-3 and Comparative Example 1 were subjected to element detection using a ThermoSCIENTIFIC Nexsa commercial X-ray photoelectron spectrometer. The test parameters were as follows: excitation source type: monochromatized Al target (E = 1486.68 eV), voltage: 12.0 kV, current: 6 mA, vacuum degree: P < 10 -8 mBar, pass energy: 150 eV (Survey), 30 eV (High-resolutions), work function: 4.20 eV. The elemental composition is the elements with obvious peaks in the XPS spectrum.

[0069] Figure 2 This is the XPS (X-ray photoelectron spectroscopy) diagram of the dark blue solid fluorescent carbon quantum dots prepared in Example 1. It can be seen that the dark blue solid fluorescent carbon quantum dots only contain carbon, oxygen and hydrogen, and do not have elements other than carbon, hydrogen and oxygen, wherein the molar ratio of carbon is 56.03%, and the molar ratio of oxygen is 43.97%. The XPS diagrams of Examples 2-3 are similar to those of Example 1. Figure 3 This is an XPS image of the carbon quantum dots prepared in Comparative Example 1. It can be seen that the carbon quantum dots contain carbon, oxygen, hydrogen and nitrogen.

[0070] Optical tests were performed on the carbon quantum dot samples prepared in Examples 1-3 and Comparative Example 1 to test their solid-state fluorescence quantum efficiency and emission spectrum. A commercial fluorescence spectrometer FLS1000 from Edinburgh, UK was used, with the parameters selected as a light source slit of 1nm and a receiver slit of 0.5nm. The carbon quantum dot sample powder was uniformly pressed into a block with a length, width and height of 10mm and a height of 2mm as a sample for testing. The quantum efficiency is the result under excitation at a wavelength of 340nm, the emission spectrum is the result under excitation at a wavelength of 340nm, and the maximum emission wavelength is the wavelength of the highest intensity point in the emission spectrum curve.

[0071] Figure 4 This is the fluorescence spectrum of the deep blue solid fluorescent carbon quantum dots prepared in Example 1 under 340nm wavelength excitation. As can be seen from the figure, its emission spectrum has a maximum emission peak of 425nm, proving that the deep blue solid fluorescent carbon quantum dots of the present invention can effectively convert ultraviolet light into deep blue light.

[0072] Table 1 shows the elemental composition, quantum efficiency and maximum emission wavelength data of Examples 1-3 and Comparative Example 1.

[0073] Table 1

[0074]

[0075]

[0076] According to Table 1, after the introduction of nitrogen, Comparative Example 1 shows no solid-state fluorescence, while Examples 1-3 all show deep blue solid-state fluorescence, and all contain only three elements: C, H, and O. And relatively speaking, Example 1 has the highest quantum efficiency of 28.81% and the bluest emission wavelength of 425nm.

[0077] Example 4

[0078] This embodiment provides an application of dark blue solid fluorescent carbon quantum dots in fluorescent color development, specifically as follows: the dark blue solid fluorescent carbon quantum dots prepared in Example 1 are directly attached to a substrate to mark the words "SUSTC", which do not emit fluorescence under sunlight, but emit dark blue light (such as 365nm ultraviolet light) under irradiation. Figure 5 Therefore, the dark blue solid fluorescent carbon quantum dots of the present invention can be used in fluorescence color development, and can be particularly used for detecting or marking objects.

[0079] In summary, the dark blue solid fluorescent carbon quantum dots provided by the present invention are composed of three elements: carbon, hydrogen and oxygen, and can emit dark blue solid fluorescent light within 450nm, and have a high solid fluorescent quantum efficiency, especially a quantum efficiency of 28% at 425nm, which can fill the gap in the field of solid fluorescent light of carbon quantum dots and enable its rapid development. In addition, the dark blue solid fluorescent carbon quantum dots of the present invention can be used in fluorescent color development.

[0080] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.

Claims

1. A deep blue solid fluorescent carbon quantum dot, characterized in that: The deep blue solid fluorescent carbon quantum dots are composed of three elements: carbon, hydrogen and oxygen, and can be excited by light of 300nm to 400nm, with a maximum emission wavelength of 420nm to 450nm.

2. The deep blue solid fluorescent carbon quantum dots according to claim 1, characterized in that: The maximum emission wavelength is 420nm to 435nm 。 3. The dark blue solid fluorescent carbon quantum dots according to claim 1, characterized in that: In the dark blue solid fluorescent carbon quantum dots, the molar ratio of carbon element is 55%-70%, and the molar ratio of oxygen element is 30%-45%.

4. The deep blue solid fluorescent carbon quantum dots according to claim 1, characterized in that: The particle size of the dark blue solid fluorescent carbon quantum dots is 3nm to 7nm.

5. A method for preparing deep blue solid fluorescent carbon quantum dots as claimed in claim 1, characterized in that: Includes steps: A precursor containing only three elements, carbon, hydrogen and oxygen, is mixed with a solvent to carry out a solvothermal reaction to obtain a crude product; The crude product is subjected to freezing and drying treatment to obtain the dark blue solid fluorescent carbon quantum dots.

6. The method for preparing dark blue solid fluorescent carbon quantum dots according to claim 5, characterized in that: The ratio of the mass of the precursor to the volume of the solvent is 0.1 g to 1 g: 10 mL to 30 mL.

7. The method for preparing dark blue solid fluorescent carbon quantum dots according to claim 5, characterized in that: The precursor is citric acid, and the solvent is an alcohol solvent or deionized water.

8. The method for preparing deep blue solid fluorescent carbon quantum dots according to claim 7, characterized in that: The alcohol solvent is methanol.

9. The method for preparing dark blue solid fluorescent carbon quantum dots according to claim 5, characterized in that: The reaction temperature of the solvent thermal reaction is 140° C. to 200° C., and the reaction time is 2 h to 12 h.

10. Use of the deep blue solid fluorescent carbon quantum dots as claimed in claim 1 in fluorescent color development.

Citation Information

Cited By

  • Low-temperature rapid macro preparation method of alpha-arbutin derived carbon quantum dots

    CN120573687A